2005
DOI: 10.1074/jbc.m502876200
|View full text |Cite
|
Sign up to set email alerts
|

Akt Activates the Mammalian Target of Rapamycin by Regulating Cellular ATP Level and AMPK Activity

Abstract: The serine/threonine kinase Akt is an upstream positive regulator of the mammalian target of rapamycin (mTOR). However, the mechanism by which Akt activates mTOR is not fully understood. The known pathway by which Akt activates mTOR is via direct phosphorylation and inhibition of tuberous sclerosis complex 2 (TSC2), which is a negative regulator of mTOR. Here we establish an additional pathway by which Akt inhibits TSC2 and activates mTOR. We provide for the first time genetic evidence that Akt regulates intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
345
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 485 publications
(379 citation statements)
references
References 48 publications
26
345
1
4
Order By: Relevance
“…In agreement, overexpression of activated Akt in Tsc2-null cells inhibits AMPK activity (Hahn-Windgassen et al, 2005). These studies suggest that the low levels of active Akt found in Tsc2-null cells are responsible for the elevated activity of AMPK.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In agreement, overexpression of activated Akt in Tsc2-null cells inhibits AMPK activity (Hahn-Windgassen et al, 2005). These studies suggest that the low levels of active Akt found in Tsc2-null cells are responsible for the elevated activity of AMPK.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies have shown that Akt inhibits AMPK, likely through a decrease of the AMP to ATP ratio through activation of glycolysis and oxidative phosphorylation (Gottlob et al, 2001;Kovacic et al, 2003;Hahn-Windgassen et al, 2005). In agreement, overexpression of activated Akt in Tsc2-null cells inhibits AMPK activity (Hahn-Windgassen et al, 2005).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Cells with elevated Akt/PKB activity showed lowered AMPactivated protein kinase (AMPK) activity, blunting its stimulating effect on TSC. Conversely, in the PKB1/ PKB2 DKO cells, AMPK activity was significantly elevated, contributing to enhanced TSC2 function (Hahn-Windgassen et al, 2005). Furthermore, it is possible that the regulation of the Akt/PKB phosphorylation sites in TSC2 -although dispensable for normal development -becomes important in a context of aberrantly elevated insulin pathway activity as in PTEN mutant situations.…”
Section: Introductionmentioning
confidence: 99%